1997
DOI: 10.1042/bj3270349
|View full text |Cite
|
Sign up to set email alerts
|

The purified and reconstituted ornithine/citrulline carrier from rat liver mitochondria: electrical nature and coupling of the exchange reaction with H+ translocation

Abstract: The mechanism and the electrical nature of ornithine/citrulline exchange has been investigated in proteoliposomes reconstituted with the ornithine/citrulline carrier purified from rat liver mitochondria. The stoichiometry of the exchanging substrates was close to 1:1. The exchange was not affected by inducing electrogenic flux of K+ with valinomycin. In contrast, the pH gradient generated by the K+/H+ exchanger nigericin in the presence of an outwardly directed K+ gradient stimulated the ornithineout/citrullin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
38
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 30 publications
1
38
0
Order By: Relevance
“…It should be noted that while arginase I is located in the cell cytosol, where ODC is also located, facilitating polyamine synthesis from ornithine, arginase II is a mitochondrial enzyme that could preferentially enhance proline or glutamate synthesis from ornithine, because ornithine aminotransferase is also located in the mitochondria (31). However, it has been shown that proline can be converted to ornithine (31) and that ornithine can be transported from the mitochondria to the cytosol (32). Consistent with our findings for H. pylori stimulation, upregulation of arginase II has been reported for RAW 264.7 cells activated by LPS (33) or cAMP (34) and in peritoneal macrophages stimulated by LPS (35).…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that while arginase I is located in the cell cytosol, where ODC is also located, facilitating polyamine synthesis from ornithine, arginase II is a mitochondrial enzyme that could preferentially enhance proline or glutamate synthesis from ornithine, because ornithine aminotransferase is also located in the mitochondria (31). However, it has been shown that proline can be converted to ornithine (31) and that ornithine can be transported from the mitochondria to the cytosol (32). Consistent with our findings for H. pylori stimulation, upregulation of arginase II has been reported for RAW 264.7 cells activated by LPS (33) or cAMP (34) and in peritoneal macrophages stimulated by LPS (35).…”
Section: Discussionmentioning
confidence: 99%
“…For example, differential expression of the arginase isoenzymes could provide a means to preferentially direct ornithine either to proline or glutamate synthesis via OAT or to polyamine synthesis via ODC (Figure 2). If so, this would imply that ornithine does not rapidly equilibrate between cytosolic and mitochondrial compartments, despite the existence of transporters via which ornithine can traverse the mitochondrial membrane [204][205][206][207][208]. So far as we are aware, no experiments to determine the effect of arginase localization on the metabolic fates of ornithine have been performed.…”
Section: Arginasementioning
confidence: 99%
“…This possibility is in accord with the notion that under physiological conditions ureagenesis depends upon mitochondrial ornithine availability and the transport of ornithine into hepatic mitochondria (24 -26). This is especially true when mitochondrial ornithine uptake is inhibited by other amino acids (26) or when the mitochondrial ornithine carrier is affected by H Ï© (27,28). Ureagenesis begins in mitochondria and finishes in the cytosol (18).…”
mentioning
confidence: 99%